Needs Analysis of English for Biomedical Laboratory Students at Medical Vocational High School of Prof. Dr. Moestopo - Ika Tri Yunianika (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The increasing number of vocational schools has contributed to the rapid expansion of English for Specific Purpose (ESP) in Indonesia. The first stage in developing learning materials for ESP is conducting needs analysis. It refers to activities in collecting information as the basis for academic development of a particular group of students. The aims of this study were to investigate and analyse the needs of students in learning English at Medical Vocational High School (SMK Kesehatan) of Prof. Dr. Moestopo. The data were collected through questionnaires and interview. The result showed that: 1). Students tend to learn English because of their needs to improve language competences than to prepare their professional job in the future, 2). Students need more practices in speaking compared to other language skills, 3). Students need materials that meets their needs, particularly in general and medical vocabulary since most of them have difficulties to understand the meaning of words, 4). The teaching method that suit to the students were based on the materials itself. It can be teachers or students centred learning. This study recommended that students need more extra times to learn English. Besides, teachers should create supportive learning environment to motivate them in study English.